Russia in the Eastern Mediterranean: Intervention, Deterrence, Containment. (12th December 2016) - Litsas, Spyridon N.
Abstract: The Syrian Civil War gave the opportunity to Russia to establish itself as a pivotal strategic element in the region of the Eastern Mediterranean. This can be seen in the Russian military presence in Syria and in the new Russian maritime strategy in the Black Sea and in the Eastern Mediterranean. This articles argues that deterrence is not enough by itself to put an obstacle in Russian regional expansionism and that a new containment policy is required in order for the West to maintain the existing status in the Eastern Mediterranean.